A definição de retórica em Platão e Aristóteles - Patriota, Murilo Henrique Barrantes (2022)
The problem that motivates this research is the definition of rhetoric given by Aristotle. If it is a “capacity to contemplate what, in each case, is believed to be persuasive” (1355b) and, still, it is considered as an “antistrophe” of dialectics, it is necessary, first, to recognize and circumscribe what is believed to be persuasive. ; second, to understand the relationship established between rhetoric and dialectics. However, to appreciate Aristotelian thinking about rhetoric, it is essential to study Plato's criticisms of art - mainly in the Phaedrus and the Gorgias - in order to reach the meaning of the Aristotelian response and its perspective on its predecessor. This appreciation is reserved for the first chapter of the work. In the second part, the main propositions of Aristotle's Art of Rhetoric are approached: the definition of rhetoric given by Aristotle and the meaning of the relationship between rhetoric and dialectics are interpreted and discussed. The method used in this investigation combines interpretive analysis of texts, philological analysis of ancient Greek concepts, a bibliographic review by commentators and specialists on the subject, a critical perspective in relation to the formation of concepts and the transmission of concepts by tradition. The hypothesis is defended that the Platonic perspective on rhetoric ends up determining the negative reception of rhetoric by the tradition, while the Aristotelian perspective produces the opposite effect. In Plato there is a clear distinction between dialectics and rhetoric with clearly opposite functions – dialectics, in Platonic philosophy, becomes the method of philosophy par excellence. It is argued that rhetoric, from the Aristotelian definition, is also an ability to contemplate the beliefs accepted by a group and, in this sense, it is not reduced to oratory, but extends to the field of philosophical reflection; rhetoric is annexed to dialectics – according to the meaning adopted for the antistrophos metaphor – and, therefore, there is not an opposition between both spheres of discursive practice, but an interdependence.